Misunderstandings Between Platelets and Neutrophils Build in Chronic Inflammation - Ramirez, Giuseppe A.; Manfredi, Angelo A.; Maugeri, Norma (Frontiers in Immunology, 2019)
Regulated haemostasis, inflammation and innate immunity entail extensive interactions between platelets and neutrophils. Under physiological conditions, vascular inflammation offers a template for the establishment of effective intravascular immunity, with platelets that offer neutrophils an array of signals that increase their activation threshold, thus limiting collateral damage to tissues and promoting termination of the inflammatory response. By contrast, persistent systemic inflammation as observed in immune-mediated diseases such as systemic vasculitides, systemic sclerosis, systemic lupus erythematosus or rheumatoid arthritis is characterised by a platelet and neutrophil reciprocal activation, which ultimately culminates in the generation of thrombo-inflammatory lesions, fostering vascular injury and organ damage. Here, we discuss recent evidence regarding the multifaceted aspects of platelet-neutrophil interaction from bone marrow precursors to shed microparticles. Moreover, we analyse shared and disease-specific events due to their aberrant deployment of the interaction in human diseases. To restore communications between the pillars of the immune-haemostatic continuum constitutes a fascinating challenge for the near future.